Degradation markers and plasticizer loss of cellulose acetate films during ageing. (October 2019) - Liu, Liu; Gong, Decai; Bratasz, Lukasz; Zhu, Zhanyun; Wang, Chengming
Abstract: Cellulose acetate (CA) was widely used by the film industry as well as by artists to create fine and decorative art. CA films plasticized with different content of diethyl phthalate (DEP) and triphenyl phosphate (TPP) were aged in different conditions for the study of the degradation markers and the plasticizer loss by means of optical microscope (OM), scanning electron microscope (SEM), X-ray diffusion (XRD), Gel Permeation Chromatography (GPC), Fourier-transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TG) and Thermogravimetric Analysis combined with Fourier-transform Infrared Spectroscopy (TG-FTIR). Degradation markers, such as changing of appearance, decreasing of molecular weight and changing of crystallinity were observed in ageing samples. At the same time, plasticizer loss of ageing samples appeared but differs among different ageing condition. In perspective, this systematic approach can be extended to the study of CA artefacts and other degradation conditions that would affect the deterioration pathways. Highlights: Degradation makers and plasticizer loss of cellulose acetate films were evaluated by several scientific methods. Changing of appearance, molecular weight, crystallinity and O–H/C–H by FTIR were observed during ageing. Plasticizer loss indicates a good correlation with ageing.